Validating Autoclave Cycles for Carcass Disposal in Animal Biosafety Level 2/3 Containment Laboratories. (September 2019) - McGirr, Rebecca; Sample, Christopher; Arwood, Leslee; Burch, James; Alderman, Scott
Introduction: Animal carcasses differ in composition from other types of solid waste, and through prior testing it was determined that cycle parameters applied to general, solid biohazardous waste did not ensure proper sterilization of ferret carcasses. Objectives: The goals of this study were to develop and validate an autoclave cycle that would ensure the decontamination of infectious animal carcasses before removal from an animal biosafety level 2/3 containment suite for downstream disposal and to test different ways to prepare and package animal carcasses for autoclaving. Methods: Intact ferret carcasses were implanted with biological indicators, and the carcasses were placed in biohazard bags, then into metal pans. To test the efficacy of the autoclave cycle on larger biomasses, 1, 2, or 4 ferret carcasses were placed in a biohazard bag. A total of 4 carcasses were placed in each pan. An autoclave cycle was created to begin the study. After initial tests, minor modifications to the initial test cycle parameters were made, and a new cycle was validated for ferret carcasses up to 2 kg each. Parameters for the validated cycle were as follows: sterilization time 240 minutes, temperature 125°C, 5 prevacuum pulses, and chamber pressure 15 psi. Results: The results of this study indicate that an extended sterilization time is required to successfully decontaminate animal carcasses compared with regular, solid, and biohazardous waste. Conclusions: This study demonstrates that it is possible to sterilize multiple intact ferret carcasses per load under validated autoclave cycle conditions.